Analisis Keefektifan Kalimat pada Kumpulan Opini untuk Literasi Statistik Edisi November 2024 sebagai Bahan Ajar Membaca Kritis - Gisa Dewantara; Anggita Fitrotunnisa Purbaningrum; Amalia Safira; Fivian Ircham Faiq; Afifah Isda Ilaiha; Asep Purwo Yudi Utomo; Riyadi Widhiyanto; Bagas Kurnianto (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Opinion is a person's opinion or thought regarding a problem that is currently occurring in society. An opinion must pay attention to the effectiveness of the sentence so that the reader can capture its contents. Therefore, this study will focus on the effectiveness of a sentence in a collection of opinions. This study was conducted to describe the effectiveness of sentences in a collection of opinions as critical reading teaching materials. This type of study is qualitative with a descriptive method; the technique for collecting data is using the listening and note-taking technique. The results of this study indicate that there are still several sentences that are not effective, so that readers have difficulty capturing their contents properly. Effective sentences meet requirements such as the economy of words, commensurate structure, logical language, and careful reasoning. Meanwhile, ineffective sentences occur because the structure of the sentence does not show unity, is wasteful of words or long-winded explanations, and lacks clarity in conveying information. The benefits of this study, in practice, are that it makes it easier for readers to determine the effectiveness of sentences in a collection of opinions. This study took data in the form of ineffective sentences contained in a collection of opinions for statistical literacy, the November 2024 edition of critical reading teaching materials for high school students.